2020
DOI: 10.3390/ma13071709
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/Poly(2-ethyl-2-oxazoline) Films with Ciprofloxacin for Application in Vaginal Drug Delivery

Abstract: Chitosan (CHI) and chitosan/poly(2-ethyl-2-oxazoline) (CHI/POZ)-based films were prepared by casting from aqueous solutions of polymer blends with different compositions. Ciprofloxacin was used as a model drug in these formulations. The weight, thickness, folding endurance and transparency of blend films were measured and characterised. All films had a uniform thickness (0.06 ± 0.01 mm) and exhibited sufficient flexibility. The surface pHs of films ranged from 3.76 ± 0.49 to 4.14 ± 0.32, which is within the pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 43 publications
0
18
0
1
Order By: Relevance
“…47 The surface characteristics of freestanding films can be fine-tuned by different post-treatment techniques. Owing to its outstanding mechanical and biological properties, chitosan nanocomposite films have already been used in various biomedical applications including wound dressing patches, [48][49][50][51] drug delivery, 52,53 implant coatings, [54][55][56] and as scaffolds. 57,58 Various nanoparticles such as nanoclay, 59 graphene, 60 silver, 61 cellulose whisker, 62 and titania 63 have been used for the preparation of chitosan nanocomposites films for such applications.…”
Section: Chitosan-based Nanocomposite Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…47 The surface characteristics of freestanding films can be fine-tuned by different post-treatment techniques. Owing to its outstanding mechanical and biological properties, chitosan nanocomposite films have already been used in various biomedical applications including wound dressing patches, [48][49][50][51] drug delivery, 52,53 implant coatings, [54][55][56] and as scaffolds. 57,58 Various nanoparticles such as nanoclay, 59 graphene, 60 silver, 61 cellulose whisker, 62 and titania 63 have been used for the preparation of chitosan nanocomposites films for such applications.…”
Section: Chitosan-based Nanocomposite Scaffolds For Tissue Engineeringmentioning
confidence: 99%
“…In addition, POZ is a non-ionic polymer, which possesses a weak mucoadhesion property. This study shows that combination of cationic and non-ionic polymer in the formulation would greatly reduce the mucoadhesive property as the non-ionic polymer occupied and decreased the concentration of the more mucoadhesive component (chitosan) [ 93 ]. Tentor et al also performed a study on the chitosan-based membrane for vaginal application.…”
Section: Novel Approaches For Vaginal Drug Delivery For Microbial mentioning
confidence: 99%
“…Both formulations from Abilova et al and Tentor et al were effective against E. coli , S. aureus , and G. vaginalis , which are the common pathogens found in BV. These studies suggested that the AC membrane and chitosan-based film are potential formulations for the management of BV [ 93 , 94 ]. Besides that, Jalil et al had developed an antimicrobial vaginal film using the thiolated gellan gum and loaded with metronidazole to treat vaginal infection.…”
Section: Novel Approaches For Vaginal Drug Delivery For Microbial mentioning
confidence: 99%
“…Часть результатов его докторской диссертации были опубликованы в виде обзора в журнале «Успехи химии» [8], в котором отражено впервые обнаруженное им явление «изоэлектрического эффекта» выталкивания в области изоэлектрической точки полиамфолитов (рисунок 3). [17], получение полимерных пленок на границе несмешивающихся жидкостей [18], теоретические исследования образования солевых связей в цепях полиамфолитов [19], разработку полимерных композиций как структурирующих агентов для предотвращения миграции радионуклидов и для их извлечения из почв [20,21], получение полимер-протектированных и гель-иммобилизованных наночастиц металлов и исследования их каталитических свойств [22,23] в качестве проточных каталитических реакторов (рисунок 7), синтез и исследования макропористых криогелей [24], синтез гидрофобно-модифицированных полимеров и гидрогелей [25], исследования по применению водорастворимых полисахаридов в нефтедобыче [26], а также создание полимерных систем доставки лекарств [27,28].…”
unclassified